Last Steps : Maurice Blanchot's Exilic Writing - Fynsk, Christopher, 1952- (Book collections on Project MUSE., 2013)
The author provides close readings of a number of Maurice Blanchot's important post-war writings. It includes chapters on Levinas and Blanchot's relation to Judaism. It attempts a form of reading that is responsive to the exorbitant challenge presented by the work of one of the most important writers and thinkers of the 20th century. It seeks to trace the possibility and lineaments of an affirmative turn that proceeds from a most trenchant refusal.